A new genus and species of a terrestrial cavernicolan planarian from Barro Colorado Island, Panama (Platyhelminthes, Tricladida, Cavernicola) - Sluys, Ronald; Laumer, Christopher (Zootaxa, 2019)
The paper provides a taxonomic description of a new genus and species of terrestrial cavernicolan triclad flatworm from Barro Colorado Island, Panama. Molecular sequences of this species were already deposited in GenBank several years ago under the provisional taxon name Cavernicola sp. Animals have the following characteristics: absence of pigmentation and eyes; mouth opening located halfway in the pharyngeal cavity; few, ventral testes extending from a position far posterior to the ovaries to directly behind the pharyngeal cavity; strongly recurving sperm ducts, thus forming a loop; horizontally oriented cone-shaped penis papilla; common oviduct oriented perpendicular to the bursal canal and opening into the latter shortly before the canal communicates with the copulatory bursa; sac-shaped copulatory bursa lacking a distinct, single lumen and filled with a mass of syncytial cells, with interspersed nuclei.